M. Ya. Ginzburg: Stylistics (1935–1945) - Zavadovsky, Petr (project baikal, 2021)
The third article of the series devoted to the stylistics of late constructivism and the role of I. I. Leonidov in its formation reviews the use and transformation of Leonidov’s patterns in the late creative works by M. Ya. Ginzburg (1935-1945). The study includes little-known and previously unpublished materials and the author’s reconstructions.